USE OF INNOVATIVE TECHNOLOGIES IN TEACHING ECOLOGY MODULE NATURAL RESOURCES - Abdrashitova E.V. (Western European Studies, 2024)
the work discusses ways to effectively use various programs and applications used in modern devices when conducting classes in the Ecology module “Natural Resources” in universities. It is no secret that students actively use various types of devices in their lives, including tablets, phones, smartphones, laptops, etc. These devices have many potential opportunities for providing educational information in a visual format with audio accompaniment
Keywords: innovative technologies; ecology; module; natural resource